Board Games Milton Bradley - Slater, Lee 1969- (Minneapolis, Minnesota Big Buddy Books, An Imprint Abdo Publishing, 2022)
Looks at the life of Milton Bradley, and how he created his board games.
Work & play -- School days -- Early career -- First game -- Making a game -- War effort -- Real life -- Kindergarten -- Hard times -- New opportunities -- The end game -- Bradley's legacy.
Includes online resources (page 31) and index.
Grades 2-3
111243
Keywords: Bradley, Milton, -- 1836-1911 -- Juvenile literature; Board games -- Juvenile literature; Inventors; Biographies; Juvenile works